Principles of practice in multi-agent systems : International Workshops: IWEC 2014, Gold Coast, QLD, Australia, December 1-5, 2014, and CMNA XV and IWEC 2015, Bertinoro, Italy, October 26, 2015, revised selected papers /: International Workshops: IWEC 2014, Gold Coast, QLD, Australia, December 1-5, 2014, and CMNA XV and IWEC 2015, Bertinoro, Italy, October 26, 2015, revised selected papers. (2016) - Unknown
No abstract available